EXPERIMENTAL VERIFICATION OF THE EFFECTIVENESS OF TEACHING THE COURSE "HISTORY OF COMPUTER SCIENCE" TO FUTURE COMPUTER SCIENCE TEACHERS - Bukanova, А.К.; Pak, Н.И. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article examines the effectiveness of teaching the history of computer science to future computer science teachers in the context of digitalization of education. The study was conducted on the basis of the Kazakh National Pedagogical University named after Abai, the Institute of Mathematics, Physics and Computer Science, for students of the specialty 6B01507–Computer Science. The research work was carried out on the basis of a pedagogical experiment consisting of three stages, namely: the first stage – ascertaining, the second stage – forming, the third stage – control. Tests, questionnaires, and essay writing were used as control and measuring materials. The analysis of the results of the experimental work is presented graphically in the form of tables and diagrams. At the stages of experimental work, the following methods were used: analysis, generalization, systematization, observation, questioning, testing, research and generalization of pedagogical experience. The effectiveness of the developed methodological system was determined by the formation of historical and information knowledge of future computer science teachers. As a result of the experimental work, the effectiveness of the methodology developed on the basis of an inverted textbook on the updated course content is checked.